LA REPRESENTACIÓN DEL MAL POR MEDIO DEL DIBUJO LIBRE TEMÁTICO EN ESTUDIANTES UNIVERSITARIOS EN CIUDAD JUÁREZ - Elsa Aranda Pastrana; Jaime Romero González; Ana Lilia López Ávila (European Scientific Journal, ESJ, 2014)
Evil is a social construction and appears with the emergence ofhuman symbolic mind; evil is an archetype that has multiple representationsthat are influenced by the environment, but its essence prevails like the onethat harms humanity. The idea of evil is a necessity for social coexistence. Itis related to Ethics, Morality and the Rights and a change in the symbolichorizon of evil could involve changes in these three areas. To know how evilis represented by the students Engineering and Technology and SocialSciences and Administration of the Autonomous University of CiudadJuárez, in 2013, where asked to draw a representation of evil. From thedrawings, an analysis and a classification were carried out on how they werestructured and the content of the drawings. 54.9% elaborated only drawings;other forms were compositions, scenes, signs and written words. In thedescription of the contents, it is important to note that 30.7 % of studentsdrew weapons and violent actions. Only 16.7 % drew devils when 74 % ofthe students recognize themselves as Christians. It can be said that studentshave changed the symbolic horizon of evil due to their violent situation inCiudad Juarez lived in the period 2007-2011.